2014
DOI: 10.1186/1475-2867-14-53
|View full text |Cite
|
Sign up to set email alerts
|

Metformin impairs growth of endometrial cancer cells via cell cycle arrest and concomitant autophagy and apoptosis

Abstract: BackgroundEffective therapies for early endometrial cancer usually involve surgical excision and consequent infertility Therefore, new treatment approaches that preserve fertility should be developed. Metformin, a well-tolerated anti-diabetic drug, can inhibit cancer cell growth. However, the mechanism of metformin action is not well understood. Here we investigate the roles of autophagy and apoptosis in the anti-cancer effects of metformin on endometrial cancer cells.MethodsIshikawa endometrial cancer cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 37 publications
(49 reference statements)
5
91
0
6
Order By: Relevance
“…These adaptor protein-ubiquitin complexes consequently depend on autophagy machinery for macromolecule clearance (37). Consistently, selective autophagy via p62 is enhanced via the autophagy agonist metformin in a dose-dependent manner, whereas silencing of autophagy with the modulator BECLIN1 attenuates the process (24). A recent study showed that HACE1 proteins play an intricate role in mediating autophagy flux by promoting optineurin-ubiquitin-p62 conjugation (38).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These adaptor protein-ubiquitin complexes consequently depend on autophagy machinery for macromolecule clearance (37). Consistently, selective autophagy via p62 is enhanced via the autophagy agonist metformin in a dose-dependent manner, whereas silencing of autophagy with the modulator BECLIN1 attenuates the process (24). A recent study showed that HACE1 proteins play an intricate role in mediating autophagy flux by promoting optineurin-ubiquitin-p62 conjugation (38).…”
Section: Discussionmentioning
confidence: 87%
“…Metformin accelerates cardiac autophagy by promoting AMPK-mediated ULK1 phosphorylation (23) and also promotes p62-mediated selective autophagic flux in a dosage-dependent manner (24). Accordingly, we asked whether PLN degradation would be affected by metformin in CMNCs.…”
Section: Resultsmentioning
confidence: 99%
“…Cantrell et al showed for the first time that metformin potently inhibits growth in two EC cell lines [half maximal inhibitory concentration (IC 50 ) of 1 mM metformin] after 72 h of treatment in a normal glucose environment (17). Takahashi et al demonstrated that after 48 h of treatment with increasing concentrations of metformin in normal glucose conditions, ≥5 mM metformin significantly reduce the number of viable cells (IC 50 of 6.78 mM metformin) (21). Furthermore, the metformin inhibitory proliferation effect has been reported for certain other types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these previous studies possessed methodological weaknesses and/or insufficient data. Additionally, experimental studies revealed that metformin is an effective antiestrogenic agent, inhibiting cell proliferation and leading to growth arrest, as well as inducing apoptosis in EC (17,(20)(21)(22). Furthermore, recent findings have suggested that metformin is important in suppressing the migration and invasion of cancer cells, which could prevent metastasis (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with metformin attenuates the estrogen-dependent proliferative expression of c-myc and c-fos in the obese rat endometrium, an effect which was accompanied by inhibition of the phosphorylation of insulin and IGF1 receptors, as well as Erk 1/2 (17,55). In vitro studies have indicated that metformin inhibits rat endometrial cell line proliferation and suppresses endometrial cancer cell growth via cell cycle arrest and concomitant autophagy and apoptosis (55,56).…”
Section: Metformin and Endometrial Cancermentioning
confidence: 99%